A systematic review comparing atypical anorexia nervosa and anorexia nervosa. Issue 4 (12th December 2022) - Walsh, B. Timothy; Hagan, Kelsey E.; Lockwood, Carlin
Abstract: Objective: A description of atypical anorexia nervosa (atypical AN) was provided in DSM‐5 in 2013 and a sizable literature has since developed describing the clinical features of individuals with atypical AN and comparing them to those of individuals with anorexia nervosa (AN) and those of healthy individuals. The purpose of this study was to conduct a systematic review of this literature. Method: A systematic review following PRISMA guidelines was conducted of studies published since 2013 that compared the clinical characteristics of individuals with atypical AN to those of individuals with AN and/or healthy controls. Meta‐analyses were conducted when similar measures were reported in three or more studies. Results: Twenty‐four publications met criteria for inclusion. Their results indicated that the level of eating disorder‐specific psychopathology is significantly higher among individuals with atypical AN than among controls and as high or higher as among individuals with AN while levels of non‐eating disorder psychopathology are similar. Individuals with atypical AN experience many of the physiological complications associated with AN, but some complications appear less frequent. Discussion: The psychological symptoms and physiological complications of individuals with atypical AN are generally similar to those of individuals with AN, although there may be differences in the frequency of some physical complications. Little information is available on the course, outcome, and treatment response of individuals with atypical AN. In addition, full diagnostic criteria for atypical AN have not been developed, and the nosological relationship of atypical AN to established eating disorders such as bulimia nervosa is unclear. Public Significance: Atypical anorexia nervosa as described in the DSM‐5 identifies individuals with many of the psychological characteristics of typical anorexia nervosa who, despite significant weight loss, are not underweight. The current systematic review found that the psychological symptoms and physiological characteristics of individuals with atypical AN are generally similar to those of individuals with AN, although there may be differences in the frequency of some physical complications. Abstract: Objetivo: En 2013 se realizó una descripción de la anorexia nerviosa atípica (ANA) en el DSM‐5 y desde entonces se ha desarrollado una literatura considerable que describe las características clínicas de los individuos que padecen anorexia nerviosa atípica y los compara con los de los individuos que padecen anorexia nerviosa (AN) y los de individuos sanos. El propósito de este estudio fue realizar una revisión sistemática de esta literatura. Método: Se realizó una revisión sistemática siguiendo las guías PRISMA de estudios publicados desde 2013 que compararon las características clínicas de individuos que padecen anorexia nerviosa atípica con las de individuos que padecen anorexia nerviosa y/o controles sanos. Se realizaron metaanálisis cuando se reportaron medidas similares en tres o más estudios. Resultados: Veinticuatro publicaciones cumplieron con los criterios de inclusión. Sus resultados indicaron que el nivel de psicopatología específica del trastorno de conducta alimentaria es significativamente mayor entre los individuos que padecen anorexia nerviosa atípica que entre los controles y tan alto o más alto como entre los individuos que padecen anorexia nerviosa, mientras que los niveles de psicopatología del no trastorno de la conducta alimentaria son similares. Los individuos que padecen anorexia nerviosa atípica experimentan muchas de las complicaciones fisiológicas asociadas con la anorexia nerviosa, pero algunas complicaciones parecen menos frecuentes. Discusión: Los síntomas psicológicos y las complicaciones fisiológicas de los individuos que padecen anorexia nerviosa atípica son generalmente similares a los de los individuos que padecen anorexia nerviosa, aunque puede haber diferencias en la frecuencia de algunas complicaciones físicas. Hay poca información disponible sobre el curso, el resultado y la respuesta al tratamiento de los individuos que padecen AN atípica. Además, no se han desarrollado criterios diagnósticos completos para la anorexia nerviosa atípica, y la relación nosológica de la anorexia nerviosa atípica con los trastornos de la conducta alimentaria establecidos, como la bulimia nerviosa, no está clara.